FUN LYRICS (FL): PENGEMBANGAN MEDIA BELAJAR BAHASA INGGRISUNTUK SISWA SEKOLAH DASAR MELALUI LIRIK MUSIK - Novi Maisaroh, Tika Novita Sari, dan Wasilatun (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
Fun Lyrics: Developing English Media for Elementary School Students through Song Lyrics is asolution to overcome the students’ difficulties in learning English. The aims of this study were 1) to designand create fun lyrics, 2) revealing the appropriateness of fun lyrics as English Learning media forelementary school students.This research employed a Research and Development method. This study was implemented throughseveral steps. They are 1) analyzing the needs, 2) designing the model, 3) implementing (coding), 4)testing the model in the field. This study was validated by the experts of media and learning materials.The feasibility test was conducted by testing the application that had been revised among the students ofSD Negeri Minggiran, Yogyakarta.The results of the study showed that fun lyrics was appropriate as media for elementary schoolstudents. Fun lyrics were designed to be interesting and combined with sounds and colours. Thebackground was yellow and in the forms of plants and animals. The song lyrics were in two languages,English and Indonesian. Based on the final validation, the model could be used easily and it wasinteresting to learn. It could improve the students’ vocabulary mastery.Key words: fun lyrics, English Learning Media, elementary school